Study On The Compatibility Of "English In Focus" Textbook For Junior High School With School Level Based Curriculum - Shofyana, Maila Huda (2012)
This research paper is mainly intended to find out whether the English textbook used for the seventh year students of Junior High School entitled "English in Focus" is compatible or not with the indicators of the language skills suggested by School Level-based Curriculum. This research applies descriptive research. In collecting data, the writer used documentary analysis as the instrument. The data were analyzed by steps; (1) presenting the materials (2) comparing the materials (3) judging whether the English textbook is appropriate with the School Level-based Curriculum or not (4) drawing conclusions. The result of the analysis shows that the percentage of the compatibility of the language skills developed in the textbook is 60,55%. It means that the textbook is good in developing language skills suggested by School Level-based Curriculum. The language skills which are developed in the textbook involve: the compatibility of listening materials are 50% or fair, the compatibility of the speaking materials are 58,82 % or good, the compatibility of the reading materials are 62,50 % or good, and 80% or very good for the writing materials. This research implies the textbook entitled "English in Focus", English Textbook for Seventh Year of Junior High School is good materials to support the learning process. The materials of listening skill in this textbook are not adequate, so the other material is needed to support the listening teaching-learning process.